The Wiley Blackwell Handbook of the Psychology of Recruitment, Selection and Employee Retention - Semedo, Carla (2018)
This handbook makes a contribution to the fields of organizational psychology and human resource management by providing comprehensive coverage of the contemporary field of employee recruitment, selection and retention.